The influence of prior practice and handedness on the orthogonal Simon effect - Iani, Cristina; Milanese, Nadia; Rubichi, Sandro (Frontiers in Psychology, 2014)
When stimuli are arranged vertically and responses horizontally, right-handed participants respond faster with right responses to stimuli presented above fixation and with left responses to stimuli presented below fixation, even when stimulus position is task-irrelevant (orthogonal Simon effect). The aim of the present work was twofold. First, we assessed whether the orthogonal Simon effect evident in right-handed participants is present also for left-handed participants (Experiment 1). Second, we investigated whether for both groups of participants the orthogonal Simon effect is influenced by the stimulus-response (S-R) mapping used for an orthogonal spatial S-R compatibility task performed five minutes before (Experiment 2). Our results showed that the orthogonal Simon effect significantly differed in the two groups, with left-handers showing an advantage for the up-left/down-right mapping (Experiment 1). Interestingly, the orthogonal Simon effect was strongly influenced by prior practice regardless of the participants’ handedness (Experiment 2). These results suggest that the short-term S-R associations acquired during practice can override the long-term, hardwired associations established on the basis of handedness.